J. Krishnamurti and Sant Kabir a study in depth - Mehta, Rohit 1908-; Mehta, Shridevi (Motilal Banarsidass, 1990)
Comparative study on the works of Jiddu Krishnamurti, 1895-1986, Indian philosopher and Kabir, 15th cent., an Indian mystic poet.